La influencia del taller "DEUTSCH LERNEN" en la producción de textos escritos en alemán en los estudiantes del quinto grado "A" de la I.E. Ofelia Velásquez - Tarapoto, 2014 - Alayo Castañeda, Gilberto Enrique (2015)
The title of this research is "INFLUENCIA DEL TALLER "DEUTSCH LERNEN" EN LA PRODUCCIÓN DE TEXTOS ESCRITOS EN ALEMÁN EN LOS ESTUDIANTES DEL QUINTO GRADO "A" DE LA l.E. OFELIA VELASQUEZ -TARAPOTO, 2014". In order to develop this investigation the following objective has been considered: to experiment the Workshop "DEUTSCH LERNEN" with the students of the 5th grade "A" of the E.I. "Ofelia Velasquez" in order to emphasize the production of written texts in the German language in 2014. With the purpose of achieving this objective, a hypothesis was stated: the Workshop "DEUTSCH LERNEN" has a significative influence in the production of written texts in German language in the students of the 5th grade "A" of the E.I. "Ofelia Velasquez" in 2014. To demonstrate the hypothesis, an applied research of the experimental level, with a pre-experimental design was developed and having a single experimental group constituted by twenty students of the 5th grade "A" of the E.I. "Ofelia Velasquez" as a sample and to whom a Pre-Test and a Post-Test before and after the experiment was administered. The date analysis of the Pre-test and the Post-test of the experimental group has allowed the researcher to demonstrate the hypothesis (H¡): There is a significative difference between the averages of the scores of the Pre and Post - Test of the experimental group. The analysis and the interpretation of the results allowed to establish that the experimentation of the Workshop "DEUTSCH LERNEN" has significantly influenced in the production of written text in German language in the students of the 5th grade "A", of the E.I. "Ofelia Velasquez", in 2014.